2017
DOI: 10.18632/oncotarget.18052
|View full text |Cite
|
Sign up to set email alerts
|

MiR-199a/b-5p inhibits hepatocellular carcinoma progression by post-transcriptionally suppressing ROCK1

Abstract: In this study, we explored the actions of miR-199a/b-5p during hepatocellular carcinoma (HCC) progression and its potential target genes. Through heatmap miRNA expression analysis of 15 matched HCC tumor and adjacent non-tumor liver tissues from the TCGA database, we detected 19 mRNAs that were upregulated and 13 that were downregulated specifically in HCC. Among these, miR-199 family members were downregulated in HCC tumors and cell lines, as compared to controls. Low miR-199a/b-5p expression was also associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 46 publications
3
38
0
Order By: Relevance
“…ROCK1 is involved in the regulation of the PI3K/AKT signalling pathway (28)(29)(30). Hence, we determined the PI3K, p-PI3K, AKT and p-AKT expression levels in Y79 and WERI-RB-1 cells cotransfected with miR-448 mimics and pcDNA3.1 or pcDNA3.1-ROCK1.…”
Section: Mir-448 Suppresses the Pi3k/akt Signalling Pathway In Rbmentioning
confidence: 99%
“…ROCK1 is involved in the regulation of the PI3K/AKT signalling pathway (28)(29)(30). Hence, we determined the PI3K, p-PI3K, AKT and p-AKT expression levels in Y79 and WERI-RB-1 cells cotransfected with miR-448 mimics and pcDNA3.1 or pcDNA3.1-ROCK1.…”
Section: Mir-448 Suppresses the Pi3k/akt Signalling Pathway In Rbmentioning
confidence: 99%
“…Several autophagy-inhibiting miRNAs, namely, miR-23b, miR-24, miR-26, miR-30a, miR-34, miR-125a, miR-141, miR-143, miR-199, miR-200 and miR-520 are found to be downregulated in cancer. Notably, these miRNAs are also known MET effectors [35][36][37][38][39][40][41][42][43][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61]85,86] . As opposed to the primary role(s) of oncomiRs, we speculate that the loss of these miRNAs allows for higher autophagy flux and suppression of MET in the DTCs to help them adapt to unfavorable settlement sites.…”
Section: Autophagy-regulating Mirnas In Cancer Metastasismentioning
confidence: 99%
“…According to our previous method [14], the obtained proteins were quantified by the BCA (Thermo Fisher Scientific, Waltham, MA, USA) method. After denaturation, equal amounts of proteins (500 ng/µL, 10 µL) from different samples were separated by sodium dodecyl sulfate polyacrylamide gel electrophoresis and transferred to nitrocellulose membranes (Millipore).…”
Section: Western Blot Analysismentioning
confidence: 99%
“…In our previous study, we found that the expression of miRNA miR-500a was significantly increased in HCC as compared to normal liver according to heat map analysis of RNA sequencing in The Cancer Genome Atlas (TCGA) database [14]. Also, previous studies have shown that miR-500a is of great interest in cancer therapies due to its association with various types of cancer, including gastric cancer [15] and prostate cancer [16].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation